Firm dynamics and real exchange rate fluctuations: does trade openness matter? ; evidence from Mexico's manufacturing sector - Miguel Fuentes; Pablo Ibarrarán (Institute for the Study of Labor (IZA), 2009)
In this paper we study the effect of NAFTA on the responsiveness of Mexican economy to real exchange rate shocks. We argue that, by opening the U.S. and Canadian markets to Mexican goods, NAFTA made it easier for domestic producers to take advantage of the opportunities brought by the depreciation of the real exchange rate. To identify this mechanism, we use plant-level data and compare the behavior of employment, production and investment after two big real exchange rate shocks: the first observed in the mid 1980s, the second the Tequila Crisis of 1994-5. The evidence indicates that after passage of NAFTA exporting firms exhibited higher growth rates of employment, sales, and investment vis-á-vis non-exporters. We confirm our results by analyzing the behavior of a control group of firms, that had complete access to the U.S. market during both devaluations, and we show that they responded in a similar way in both events. Finally, we also provide direct evidence on the relationship between exports and tariff reductions brought by NAFTA. Our results support the view that NAFTA has allowed Mexican producers to respond more quickly to real exchange shocks.
Keywords: F36; F41; 330; NAFTA; RER shocks; Tequila crisis; external adjustment; firm-level evidence of effects of RER shocks; Kaufkraftparität; Schock; Verarbeitendes Gewerbe; Außenhandelsliberalisierung; Mexiko; NAFTA-Staaten